Poczet Rektorów Uniwersytetu Warszawskiego - Gawkowski, Robert (University of Warsaw Press, 2025)
This publication fills a significant gap in our knowledge about the most important figures of the University of Warsaw. Until now, there has been no comprehensive study of all the rectors' biographies. For example, the period of the Imperial University of Warsaw was omitted from the lists of rectors. The author has done a tremendous amount of archival work, drawing information from, among other sources, personnel files stored in the New Records Archive, the Polish Academy of Sciences Archive, the Warsaw Medical University Archive, and the University of Warsaw Archive. The texts focus on the period during which their protagonists held the position of rector or worked at the University of Warsaw. The author's primary aim was to ensure that the character of the individual was not lost in the maze of his achievements. He therefore avoided listing all the dignities, medals, honors, and functions, instead sketching vivid portraits of interesting personalities from Warsaw's scientific community.